Trust-Based Selling (Audio Book) - Green, Charles (McGraw-Hill, 2005)
Sales based on trust are uniquely powerful. Learn from Charles Green, co-author of the bestseller The Trusted Advisor how to deserve and, therefore, earn a buyer's trust. Buyers prefer to buy from people they trust. However, salespeople are often mistrusted. Trust-Based Selling shows how trust between buyer and seller is created and explains how both sides benefit from it. Heavy with practical examples and suggestions, the book reveals why trust goes hand-in-hand with profit; how trust differentiates you from other sellers; and how to create trust in negotiations, closings, and when answering the six toughest sales questions. Trust-Based Selling is a must for anyone in sales, is especially invaluable for sellers of complex, intangible services.